Measuring and analysing the use of ontologies : a semantic framework for measuring ontology usage /: a semantic framework for measuring ontology usage. ([2018]) - Ashraf, Jamshaid; Hussain, Omar K; Hussain, Farookh Khadeer; Chang, Elizabeth J
No abstract available